International movement of prisoners - Mulgrew, Roisin (Springer, 2011)
This article analyses and compares the evolution of the procedures and motivations for the international movement of prisoners under two systems operating in the United Kingdom – the inter-state prisoner transfer system and the international criminal justice enforcement system. It sets out the basic conditions for transfers under the current systems before outlining recent changes in the inter-state system to the requirement to obtain the consent of the proposed transferee (the prisoner) and the state that will implement the sentence. It proceeds to discuss the potential consequences and benefits these procedural modifications may entail for both systems. The paper concludes by evaluating the different and changing rationales used to justify the international movement of prisoners.